1992
DOI: 10.1111/j.1471-0528.1992.tb14474.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum screening for Down's syndrome: the effect of routine ultrasound scan determination of gestational age and adjustment for maternal weight

Abstract: Objective To investigate the effect of using a routine ultrasound estimate of gestational age and maternal weight adjustment on maternal serum alpha‐fetoprotein (AFP), unconjugated oestriol (uE3) and human chorionic gonadotrophin (hCG) levels in antenatal screening for Down's syndrome. Design Women with a singleton pregnancy without Down's syndrome were screened using the three serum markers and an estimate of gestational age based on ‘dates’ (time since first day of the last menstrual period) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
97
1
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(102 citation statements)
references
References 11 publications
3
97
1
1
Order By: Relevance
“…The 10th centile and 90th centile for AFP and UE] and the data related to our Tables 4 and 51 show similarity with data published previously by Wald et al 15 as shown in Table 1. If, therefore, our population parameters in our earlier Table 6 are closer to the consensus estimates for AFP and The real test of any screening programme is not based on mathematical modelling of retrospective data and adjustments or estimates of the 'real world', but is based on true prospective experience.…”
Section: Pointsupporting
confidence: 80%
See 1 more Smart Citation
“…The 10th centile and 90th centile for AFP and UE] and the data related to our Tables 4 and 51 show similarity with data published previously by Wald et al 15 as shown in Table 1. If, therefore, our population parameters in our earlier Table 6 are closer to the consensus estimates for AFP and The real test of any screening programme is not based on mathematical modelling of retrospective data and adjustments or estimates of the 'real world', but is based on true prospective experience.…”
Section: Pointsupporting
confidence: 80%
“…When the actual data is examined, the median Free (3-hCG in Down's syndrome cases at the [14][15][16] weeks' gestation period was 2·52 and at greater than 16 weeks was 2' 32. The corresponding median for AFP in these two groups was o· 66 and 0'73 and the mean age was 30·9 and 30'2 years, respectively.…”
Section: Pointmentioning
confidence: 99%
“…AFP concentrations were converted into multiples of the median (MoMs) using regression equations for gestational age based on either days from the last menstrual period (dates) or the biparietal diameter measurement from an ultrasound scan, as previously described. 7 Corrections were also made for maternal weight.…”
Section: Methodsmentioning
confidence: 99%
“…Estimates of the parameters derived from these data are shown in Table 1 together with those derived by Wald. 4 The latter have been chosen for illustrative purposes as they are widely used. Others we could have used include those of Crossley, 2 Spencer 5 and Heyl.…”
Section: Subjectsmentioning
confidence: 99%